APPARENT POLYTYPISM IN THE RUIZ PEAK FERRIC PHLOGOPITE - Nespolo M.; Kuwahara Y. (My University, 2001)
An example of apparent polytypism in micas, i.e. twinning ofa polytype giving a diffraction pattern which simulates that of a different polytype with longer periodicity, is reported from the Ruiz Peak ferric phlogopite, which is well known for the large number of polytypes and twins already found. The X-ray diffraction pattern, precession method, may correspond to a 1M polytype twinned by reticular pseudo-merohedry, a 3T polytype, untwinned or twinned by complete merohedry, or a 1M-3T allotwin. The morphological observation under the polarising microscope clearly shows the presence of twinning with composition plane (001) (rotation twinning), ruling out the case of untwinned 3T polytype. The SPM observation of the surface reveals the presence of 10 Angstrom steps, without interlacing pattern or multiple steps, indicating that the sample is a twin of 1M. The twin is law [310](pi) (or [3 (1) over bar0]pi), the twin index is 3, and the twin obliquity is 0.03 degrees. The higher frequency of rotations twins, i.e. with composition plane (001), with respect to reflection twins, i.e. with composition plane (quasi) normal to (001), is discussed in terms of the crystal growth conditions.